PERANCANGAN E-KATALOG PADA PERPUSTAKAAN DIGITAL STT-PLN BERBASIS WEB: Yessy Fitriani, Yasni Djamain, Risalatulina Dwi Kurniati - Jurnal, Redaksi Tim (PETIR, 2019)
STT-PLN library has had a website before, but there is no catalog features whose books have not owned by the library STT-PLN. This research will discuss about how to design the development of perpusatakaan digital STT-PLN in the added features of e-catalogs. The application of research methods using User Centered Design (UCD). In this application development using UML (Unified Modeling Language) diagram for designing the research development of perpusatakaan digital STT-PLN which includes use case diagrams, class diagrams, activity diagrams, and sequence diagrams. Solving the problem of system design include database design, application menu hierarchy and application interface design. UML which has been designed and then translated into web-based programming language that is PHP and using MySQL as the database. Then the last application tested using the User Acceptance Test (UAT), the direct testing of applications by users of the application. Implementation of the development of perpusatakaan digital is obtained results of a dynamic web based applications that can help users in accessing library applications online through the Internet and to members can facilitate the conduct of order books online, as well as facilitate the administrator library to manage the application.